Analisis Pengaruh Emisi Karbon, Kinerja Keuangan, Eco-Efficiency dan Green Innovation Terhadap Nilai Perusahaan dengan Kinerja Lingkungan Sebagai Variable Moderasi: Studi Perusahaan Sektor Energy di Bursa Efek Indonesia Periode 2019-2023 - Elizabeth Parulian Damanik; Wiwik Prihandini (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This research aims to analyze the influence of carbon emission disclosure, financial performance, eco-efficiency, and green innovation on company value, with environmental performance as a moderating variable. Secondary data was collected through documentation techniques from sustainability reports and annual reports of companies listed on the Indonesia Stock Exchange during the period 2019 to 2023. The analysis method used was multiple linear regression with the help of the Eviews application. The research results show that disclosure of carbon emissions and financial performance has a significant positive influence on company value. Apart from that, eco-efficiency and green innovation also contribute to increasing company value. Environmental performance as a moderating variable is proven to strengthen the relationship between carbon emission disclosure and company value, as well as between financial performance and company value. These findings provide empirical contributions to the accounting and business practice literature, and encourage companies to increase transparency in disclosing environmental information in order to achieve higher corporate value.